Transgenic animals: catalysts in drug discovery (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Transgenic technologies have fundamentally transformed scientific research by enabling precise genetic modifications with wide-ranging applications across various fields. This review examines the application of transgenic mice across various research domains including cancer, diabetes, cardiovascular science, neurology, gastrointestinal research, and reproductive science. We explored how these models are important in enhancing the knowledge of complex biological methods, from elucidating pathways of the disease to enhancing the quality of research outcomes in these fields. Key methodologies such as CRISPR-Cas9, TALENs, knock-out, knock-in, microinjection, embryonic stem (ES) cell transfection are highlighted, with a focus on their impact on experimental results. Additionally, the review addresses the use of various transgenic strains in drug discovery and the challenges associated with transgenic research. By integrated findings from multiple research areas, this review underscores the transformative potential of transgenic technologies and their pivotal role in driving innovation and addressing global challenges.